Economic Risk Linkages between Israel and Middle East Countries - Kirikkaleli, Dervis; Yorucu, Vedat (Savez Ekonomista Vojvodine, 2018)
This study analyses the economic risk relationship between seven of the top economies in the Middle East and Israel. Our findings are of great interest and likely to begin a new debate in the Middle East region. The results of a block exogeneity Wald test reveal that economic stability in Israel does Granger-cause economic stability in Lebanon, Oman, Qatar and the UAE. Reverse causality has been validated for Lebanon and Bahrain only. We also find that there is a positive impact on Israel's economic stability over the stability of Bahrain, Kuwait and the UAE with different seasonal patterns. In the reverse direction, in response to a shock to Israel's economic stability, the stability of the UAE, Saudi Arabia, Oman, and Kuwait are also found to be positive and significant with different seasonal frequencies.
Keywords: Israel; Middle East; Economic risk; Block exogeneity Wald test; Generalized impulse response function